Pengaruh Insentif terhadap Tingkat Disiplin Kerja Karyawan di PT. Perkebunan Nusantara III (Persero) Medan - Syahputra, Rizaldy; Miftahuddin, Miftahuddin; Laili KS, Isnaniah (Economics, Business and Management Science Journal, 2024)
This study aims to determine the impact of incentives on the level of employee work discipline at PT. Perkebunan Nusantara III (Persero) in Medan. The research conducted is quantitative, aiming to identify the influence or relationship between independent and dependent variables, the strength of the influence or relationship, and to determine the correlation between independent variables. The study's population consists of 50 individuals, sampled using a saturated sample, and with 50 participants serving as respondents. The research results from the t-test indicate that the calculated t for incentives is 7.418, exceeding the t-table value of 1.677, with a t probability (sig) of 0.000, smaller than the significance threshold of 0.05. This demonstrates that incentives, partially, significantly influence work discipline at PT. Perkebunan Nusantara III Medan. Based on the coefficient of determination, the Adjusted R Square value obtained is 0.524. To ascertain the magnitude of the influence of independent variables on the dependent variable, the coefficient of determination (KD) can be calculated as R2 x 100%, yielding a KD of 52.4%. This suggests that 52.4% of work discipline (dependent variable) can be explained by the incentive variable, while the remaining 47.6% is influenced by other factors not accounted for in this study.